2019
DOI: 10.1371/journal.pone.0214590
|View full text |Cite
|
Sign up to set email alerts
|

Long acting reversible contraception use and associated factors among married women of reproductive age in Nepal

Abstract: Modern contraceptives are highly effective and proven means of preventing unintended pregnancy and reducing maternal mortality. Social and economic characteristics are some of the key determinants of health and utilization family planning. However, studies examining the factors associated with utilization of long acting reversible contraception (LARC) are limited in Nepal. This study assessed the factors associated with utilization of LARC methods among married women of reproductive age in Nepal. Secondary dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 22 publications
(28 reference statements)
9
53
5
3
Order By: Relevance
“…The women who belonged to households in the highest wealth quintile were less likely to use LARC compared to women who belonged to the lowest wealth quintile. The study contradicts ndings in Nepal, Ethiopia, Iran and Nigeria [18,42,46,47], as these studies found a positive association between LARC use with higher wealth quintile.…”
Section: Bivariate Analysiscontrasting
confidence: 75%
See 3 more Smart Citations
“…The women who belonged to households in the highest wealth quintile were less likely to use LARC compared to women who belonged to the lowest wealth quintile. The study contradicts ndings in Nepal, Ethiopia, Iran and Nigeria [18,42,46,47], as these studies found a positive association between LARC use with higher wealth quintile.…”
Section: Bivariate Analysiscontrasting
confidence: 75%
“…The low Contraceptive Prevalence Rate (CPR) of 6.8% reported in Nigeria in 1999 [18], and currently, 17% [19] is the direct cause of the high abortion rate [20]. Contraceptive empowers women and couples to make decisions about the timing and spacing of pregnancies [21], and it also can prevent one in every three maternal deaths by allowing women to space births, avoid unintended pregnancies and abortions, and stop childbearing when they achieve their preferred family size [18,20,22] because it's their right to have access to modern contraceptive and maternal health care regardless of age, income, marital status, and parity [23]. The unfettered access and use of effective methods of contraception, especially the Long-Acting Reversible Contraceptives (LARC), will help to reduce this global burden of disease and mortality emanating from unsafe abortion [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2017, IUDs and implants were used by only less than 10% of women in reproductive age. Gallo, 2019;Austad, Shah, & Rohloff, 2018;Bhandari, Pokhrel, Gabrielle, & Amatya, 2019;Dempsey, Billingsley, Savage, & Korte, 2012;Finer, Jerman, & Kavanaugh, 2012;Harzif, Mariana, Malik, Silvia, & Lovita, 2019;Weber, Briggs, & Hanson, 2017), parity (Asad et al, 2019;Bhandari et al, 2019;Finer et al, 2012;Mazzei et al, 2019), family welfare (Adedini et al, 2019;Bhandari et al, 2019;Fekadu, Omigbodun, Roberts, & Yalew, 2019), women's knowledge (Dempsey et al, 2012;Harzif et al, 2019;Mazzei et al, 2019), women's education (Adedini et al, 2019;Asad et al, 2019;Mazzei et al, 2019;Ontiri et al, 2019;Secura & McNicholas, 2013), husband education (Bhandari et al, 2019), women's occupation (Adedini et al, 2019;Fekadu et al, 2019), husband's occupation (Bhandari et al, 2019), religion (Mazzei et al, 2019;Ontiri et al, 2019), desire for children in the future (Bhandari et al, 2019;Ontiri et al, 2019), accessibility (Secura & McNicholas, 2013) were documented as significant predictors of LARC used. Health related factors for LARC adoption were health workers skills (Harzif et al, 2019;Ontiri et al, 2019), counselling (Mazzei et al, 2019;Secura & McNicholas, 2013) and history of abortion (Fekadu et al, 2019)…”
Section: Introductionmentioning
confidence: 93%